2021
DOI: 10.1007/s12665-021-09802-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel tree-based algorithm for real-time prediction of rockburst risk using field microseismic monitoring

Abstract: Rockburst is a kind of complex and catastrophic dynamic geological disaster in the development and utilization of underground space, which seriously threatens the safety of personnel and environment. Due to the suddenness in time and randomness in space, the prediction of rockburst becomes a great challenge. Microseismic monitoring is capable to continuously capture rock microfracture signals in real time, which offers an effective means for rockburst prediction. With the explosive growth of monitoring data, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Te gestation process of coal mine earthquake was a growth process of stress, strain, and energy in the hypocenter area. Te coal mine earthquake occurred when the stress or energy in the hypocenter area reaches critical stress or energy of coal mine earthquake [45][46][47][48]. Te strain growth in the hypocenter area during gestation of coal mine earthquakes includes the elastic strain and inelastic strain [49].…”
Section: Analysis Of the Coal Mine Earthquake Gestation Process Based...mentioning
confidence: 99%
“…Te gestation process of coal mine earthquake was a growth process of stress, strain, and energy in the hypocenter area. Te coal mine earthquake occurred when the stress or energy in the hypocenter area reaches critical stress or energy of coal mine earthquake [45][46][47][48]. Te strain growth in the hypocenter area during gestation of coal mine earthquakes includes the elastic strain and inelastic strain [49].…”
Section: Analysis Of the Coal Mine Earthquake Gestation Process Based...mentioning
confidence: 99%
“…In the elevation range of 450-530 m, MS events continue to gather, and the emergence of Cluster 5 indicates a strengthening connection between the mining area and the surface fractures. Variance analysis was used to assess the differences between different clusters [31][32][33][34][35]. Pairwise comparisons between different clusters were conducted using t-tests, and the results are presented in Table 2.…”
Section: Cluster Analysis Of Roof Collapse Ms Eventsmentioning
confidence: 99%
“…The p-value for the comparison between Cluster 2 and Cluster 6 is 0.2252, suggesting nonsignificance, likely because Clusters 2 and 6 overlap spatially Based on the field measurements, it can be concluded that the grouping of these two com ponents is reasonable. Variance analysis was used to assess the differences between different clusters [31][32][33][34][35]. Pairwise comparisons between different clusters were conducted using t-tests, and the results are presented in Table 2.…”
Section: Cluster Analysis Of Roof Collapse Ms Eventsmentioning
confidence: 99%
“…Adoko et al predicted rock pressure strength through the use of a fuzzy reasoning system, adaptive neurofuzzy reasoning system, and field measurement data [ 9 ]. Xin proposed a new tree-based algorithm that introduced artificial intelligence to improve the prediction ability, automatically identify precursor microseismic sequences, and forecast the rock pressure strength in real-time [ 10 ]. Bagaraja combined energy balance and induced stress to predict occurrences of rock bursts [ 11 ].…”
Section: Introductionmentioning
confidence: 99%